Pulmonary Function and Aerobic Capacity Responses to Equine Assisted Therapy in Adolescents with Idiopathic Scoliosis: A Randomized Controlled Trial - Mohamed A. Abdel Ghafar; Osama R. Abdelraouf; Amr A. Abdel-aziem; Tamer E. Elnegamy; Mariam E. Mohamed; Amr M. Yehia; Gihan Samir Mousa (Medical Journals Sweden, 2022)
Background: Idiopathic scoliosis is a common spinal malalignment that negatively impacts the respiratory system and physical conditioning in adolescents. Equine-assisted therapy comprises therapeutic horseback riding that optimizes physical performance and mobility in a range of contexts. However, the influence of equine-assisted therapy on pulmonary function remains unclear. Objective: To examine the impact of 10 weeks of hippotherapy combined with Schroth exercises on pulmonary function and aerobic capacity in adolescents with idiopathic scoliosis. Methods: A randomized controlled trial including 45 patients, randomly assigned to experimental and control groups, was performed. Patients in the experimental group received 15 30-min sessions of hippotherapy over a period of 10 weeks. The 2 groups attended a 60-min session of Schroth exercises 3 times/week for 10 weeks. Pulmonary function and functional capacity were assessed before and after the intervention. Results: Pre- and post-intervention variables (FVC, FEV1, FEV1/FVC, MVV and 6MWT) revealed significant improvement in both groups (p < 0.05). The improvement in the experimental group was significantly higher than in the control group (p < 0.05). Conclusion: The addition of hippotherapy to Schroth exercises resulted in improved pulmonary function and aerobic capacity in adolescents with idiopathic scoliosis. LAY ABSTRACT Scoliosis is a 3-dimensional spine deformation disorder that has direct consequences on the thoracic cage, resulting in lung constriction and functional difficulties in adolescents. Conservative therapy approaches are mostly designed to correct the spinal bony curvature rather than address adverse negative deterioration. This study investigated the effect of hippotherapy (equine therapy) in combination with Schroth exercises on pulmonary function and aerobic capacity in adolescents with idiopathic scoliosis. The combination of hippotherapy with Schroth exercises had a significant benefit compared with Schroth exercises alone. Horseback riding therapy could be an innovative complementary physical therapy technique for improving respiratory and physical functioning in adolescents with idiopathic scoliosis.